Effect of maternal and child factors on stunting: partial least squares structural equation modeling - Agus Santosa; Essa Novanda Arif; Dinal Abdul Ghoni (The Korean Pediatric Society, 2022)
Background Stunting is affected by various factors from mother and child. Previous studies assessed only one or more influencing variables. Unfortunately, nor the significant influence of maternal and child factors nor the indicators contributing to maternal and child factors that affect the stunting incidence have ever been analyzed. Purpose This study analyzed the effect of maternal and child factors on stunting and the significant indicators that shape the maternal and child factors that impact stunting. Methods This was a case-control study. Overall, 132 stunted children and 132 nonstunted children in Purbalingga Regency, Central Java Province, participated in the research. Direct interviews and medical record reviews were conducted to assess the studied variables. The research data were tested using the partial least squares structural equation with a formative model. Results Maternal factors directly affected the occurrence of stunting (t=3.527, P<0.001) with an effect of 30.3%. Maternal factors also contributed a significant indirect effect on stunting through child factors (t=4.762, P<0.001) with an effect of 28.2%. Child factors affected the occurrence of stunting (t= 5.749, P<0.001) with an effect of 49.8%. The child factor was influenced by maternal factor with an effect of 56.7% (t=10.014, P<0.001). The moderation analysis results demonstrated that maternal and child factors were moderate predictive variables of stunting occurrence. Conclusion Child factors have more significant and direct effects on stunting than maternal factors but are greatly affected by them.